Social Determinants of Addiction in Middle-aged Population in Yazd - Javad Kheirandish; Mohammad Hassan Lotfi; Hossein Fallahzadeh; Mohammad Hadi Farahzadi; Seyed Mohammad Hossein Hosseini; Mohammad Milad Mehrabanian (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: There are several determinants involved in drug abuse, some of which, especially social factors, can be changed and corrected; therefore, more effective prevention programs can be implemented by recognizing them. This case study aimed to determine the social factors of addiction in middle-aged population living in Yazd city. Methods: In this case-control study conducted during 2019- 2020, 150 substance users who referred to methadone maintenance treatment centers (MMTCs) were involved in a case group and 150 subjects, matched in terms of sex and age, were selected as a control group. The cases were selected by cluster sampling method from Yazd MMTCs. The witnesses were selected from the neighbors of the cases. The data collection tool was a researcher-made questionnaire that consisted of three parts, including demographic questions, economic and social factors, and substance abuse-related questions. The content validity of the questionnaire was confirmed by experts and its reliability by Cronbachchr('39')s alpha coefficient which was 0.75. The cases were selected by cluster sampling from MMTCs. The data were analyzed using SPSS software and Binary logistic regression model was used to find the related characteristics. Results: The results of logistic regression model showed that individuals working in non- profit organizations had the highest share in relation to substance user, with an odds ratio of 4.65 (OR=4.65,95%CI:1.4-15.38,P=0.01). The use of drugs, substance user's first-degree relatives, and substance user's friends with odds ratios of (OR=3.4,95%CI:1.87-6.2,P=0.0001), (OR=2.97,95%CI:1.5-6.03,P=0.002), and (OR=2.6, 95%CI:1.43-4.75,P=0.002). respectively, were significantly related to substance user  and had the highest risk for substance user. (P = 0.0001). Conclusion: The results of this study indicated that substance users had more social risk factors compared to the general population. Therefore, planned measures to reduce these risk factors among the community, especially young people and their friends, by family, and community officials are necessary. Family plays a decisive role in choosing a friend for their children.